Concepts and Constructs for Personal Branding: An Exploratory Literature Review Approach - Zarkada, Anna K. (My University, 2012)
Personal branding is a new marketing concept related to the marketing strategies that a person adopts in order to promote his or her major personal characteristics. Personal branding is heavily used by celebrities politicians, and people who look for social integration, support or uniqueness. The personal branding phenomenon is a relatively new phenomenon for western societies, lately studied by sociologists as well as marketers. As a new social phenomenon and marketing construct, the academic marketing literature examining it is still under-developed. The present paper aims to present a literature review of the popular press and academic marketing perspective and attempts to define the construct and set a research agenda to identify the variables of the personal branding construct.
Keywords: Personal branding; Literature Review; Branding